2006
DOI: 10.1111/j.1365-2443.2006.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient alterations in granule cell proliferation, apoptosis and migration in postnatal developing cerebellum of CRMP1−/– mice

Abstract: Collapsin response mediator proteins (CRMPs) consist of five homologous cytosolic proteins that participate in signal transduction involved in a variety of physiological events. CRMP1 is highly expressed during brain development; however, its functions remains unclear. To gain insight into its function, we generated CRMP1 -/-mice with a knock-in LacZ gene. No gross anatomical changes or behavioral alterations were observed. Expression of CRMP1 was examined by the expression of the knocked-in LacZ gene, in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 55 publications
3
46
0
2
Order By: Relevance
“…3D). In adult Reln rl/rl cerebellum, the number of granule cells was reduced, and transient reduction of granule cells was observed in crmp1 Ϫ/Ϫ cerebellum (Rice et al, 1998;Charrier et al, 2006). We found that loss of crmp1 in a dab1 heterozygous background led to the disruption of hippocampal lamination, a Reeler-like phenotype (Fig.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…3D). In adult Reln rl/rl cerebellum, the number of granule cells was reduced, and transient reduction of granule cells was observed in crmp1 Ϫ/Ϫ cerebellum (Rice et al, 1998;Charrier et al, 2006). We found that loss of crmp1 in a dab1 heterozygous background led to the disruption of hippocampal lamination, a Reeler-like phenotype (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…yotari mice were spontaneous mutants at the dab1 allele (Yoneshima et al, 1997). sema3A and crmp1 mutant mice were generated as described previously (Taniguchi et al, 1997;Charrier et al, 2006). Genotypes of the offspring of all mutant mice were assessed using PCR, as described previously (D'Arcangelo et al, 1997;Kojima et al, 2000;Sasaki et al, 2002;Charrier et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…cdk5, sema3A, and crmp1 mutant mice were generated as described previously (Ohshima et al, 1996;Taniguchi et al, 1997;Charrier et al, 2006). Genotypes of the offsprings of all mutant mice were assessed using polymerase chain reaction as described previously (Ohshima et al, 1996;Sasaki et al, 2002;Charrier et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Unphosphorylated CRMPs bind with tubulin heterodimer, whereas phosphorylation of CRMPs by Rho/ROCK kinase, cyclin-dependent kinase-5 (Cdk5) and glycogen synthase kinase-3␤ (GSK-3␤) lowers the binding affinity of CRMPs to tubulin (Fukata et al, 2002;Uchida et al, 2005). Recently, several knock-out mice studies demonstrated that the loss of CRMPs causes impaired cell migration, dendritic patterning and spine development (Charrier et al, 2006;Yamashita et al, 2006;Su et al, 2007;Yamashita et al, 2007;Quach et al, 2008), suggesting that CRMPs play an important role in the development of nervous system in vivo.…”
Section: Introductionmentioning
confidence: 99%